RETRACTED: Change of water-physical properties of mountainous meadow-chernozem soils of the republic of Armenia under the influence of anthropogenic factor - Kroyan Samvel; Tovmasyan Suren; Efendyan Paruyr; Margaryan Anush (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001